AGENCY THEORY’S EFFECT ON THE SUCCESS OF TOTAL QUALITY MANAGEMENT AND FIRM PERFORMANCE (Singaporean Journal of Business Economics and Management, 2017)
The paper relates that, the mixed view on TQM and performance link is attributed to agency problems that hamper total quality management implementation. The study shows that, the inconsistencies are due to the inconsistent responsiveness of the application of agency cost control mechanisms for different managers (agents) with different behavioural traits. The paper offers testable propositions on TQM success and agency cost hypothesis. Contributing to agency theory-cost control mechanisms (ACCM), the paper proposes a behavioural equilibrium mix where t wo opposing views between Jensen and Brennan are superimposed to produce the equilibrium behaviour point where management become responsive to ACCM.